Analysis of Systems Ensuring the Acquisition of Real-Time Cartographic Navigation Information - Goreļikovs Dmitrijs (Transport and Aerospace Engineering, 2019)
Electronic Chart Display and Information Systems (ECDIS), which are used on vessels and can replace paper charts, allow to obtain and display on electronic charts information from basic and additional data sources. For the certified use of ECDIS instead of paper charts, it is necessary to ensure constant updating of Electronic Navigation Chart (ENC) data provided to vessels for use. The known visual and satellite observation systems intended for cartographic information update are costly, have low accuracy and do not allow to quickly update navigational charts in real-time mode. The stand-alone use of remotely piloted aircraft (RPA) will make it possible not only to substantially reduce costs and increase the accuracy of monitoring, but also to provide information in real-time mode.